Introductory soil science - Negi, S. S. (Daehradun, 1983)
This short work includes chapters on Soil-formation, composition, texture, structure; Soil horizons; Soil types of India; Manures and Fertilizers etc. Broadly speaking, the syllabus of 'Forest Soils' as prescribed for the Indian Forest College and the State Forest Service Colleges have been covered. During the writing of this volume.
Keywords: Soil Science; IFoS as an author; Indian Forest Service